Yield attributes and yield in somaclones of ginger (Zingiber officinale Rosc.) - Sankar, A Dev, A Kurian, M A (Journal of Spices and Aromatic Crops, 2016)
Twenty five somaclones derived from two induced polyploids (Z-0-78 and Z-0-86) and diploid cultivar ‘Himachal Pradesh’ were field evaluated and subjected to yield and yield attribute analyses. Somaclones were highly variable in the yield and yield attributes. Extent of variation was more in somaclones when compared to check varieties (Karthika and IISR-Varada) rather than parent cultivars (Z-0-78, Z-0-86 and HP). Somaclones derived from Z-0-86 recorded superiority in rhizome characters over those derived from ‘Himachal Pradesh’ and Z-0-78. About 92% of somaclones showed higher yield over parent cultivars while 84% of somaclones showed higher rhizome yield over check varieties. Somaclones derived from Z-0-86 alone recorded higher driage and dry yield.